A scenario for impacts of water availability loss due to climate change on riverine fish extinction rates. Issue 5 (15th July 2013) - Tedesco, Pablo A.; Oberdorff, Thierry; Cornu, Jean‐François; Beauchard, Olivier; Brosse, Sébastien; Dürr, Hans H.; Grenouillet, Gaël; Leprieur, Fabien; Tisseuil, Clément; Zaiss, Rainer; Hugueny, Bernard; Bode, Michael
Summary Current models estimating impact of habitat loss on biodiversity in the face of global climate change usually project only percentages of species 'committed to extinction' on an uncertain time‐scale. Here, we show that this limitation can be overcome using an empirically derived 'background extinction rate–area' curve to estimate natural rates and project future rates of freshwater fish extinction following variations in river drainage area resulting from global climate change. Based on future climatic projections, we quantify future active drainage basin area losses and combine them with the extinction rate–area curve to estimate the future change in extinction rate for each river basin. We then project the number of extinct species in each river basin using a global data base of freshwater fish species richness. The median projected extinction rate owing to climate change conditions is c. 7% higher than the median background extinction rate. A closer look at the pattern reveals great geographical variations highlighting an amplification of aridity by 2090 and subsequent increase in extinction rates in presently semi‐arid and Mediterranean regions. Among the 10% most‐impacted drainage basins, water availability loss will increase background extinction rates by 18·2 times (median value). Projected numbers of extinct species by 2090 show that only 20 river basins among the 1010 analysed would experience fish species extinctions attributable to water availability loss from climate change. Predicted numbers of extinct species for these rivers range from 1 to 5. Synthesis and applications. Our results strongly contrast with previous alarming predictions of huge surface‐dependent climate change–driven extinctions for riverine fishes and other taxonomic groups. Furthermore, based on well‐documented fish extinctions from Central and North American drainages over the last century, we also show that recent extinction rates are, on average, 130 times greater than our projected extinction rates from climate change. This last result implies that current anthropogenic threats generate extinction rates in rivers far greater than the ones expected from future water availability loss. We thus argue that conservation actions should be preferentially focused on reducing the impacts of present‐day anthropogenic drivers of riverine fish extinctions.